(untitled) (World Bulletin of Social Sciences, 2025)
The family, as a small unit of social society, reflects the national characteristics of a particular people, nation or ethnic group, as well as the content of the existing system. The strength of families, their achievement of harmony and prosperity is determined by the economic and spiritual development of the social system to which they belong, the spiritual and moral standards practiced in society, and the content of state policy. In turn, the spiritual image of society depends on the result and effectiveness of social education organized in families. In this process, the teacher creates conditions for the development, formation, acquisition of knowledge and upbringing of the individual, and at the same time performs the function of management and guidance. In the educational process, the student becomes the main figure. Knowledge, experience and interactive methods of pedagogical technology and pedagogical skills ensure that students acquire knowledgeable, mature skills. So, modern pedagogical technology is an educational event that meets all the requirements of the above conditions